Citrobacter sedlakii – A rare cause of meningitis and brain abscess in a neonate - Tripathi, Shalini; Chauhan, Avantika; Kumar, Mala; Shukla, Suruchi; Chitiz Srivastava, (Indian Journal of Child Health, 2020)
Citrobacter sedlakii is a Gram-negative bacillus, usually a non-pathogenic organism, found in human stool. However, it may rarely cause devastating illness in human beings. We are describing a case of C. sedlakii meningitis and brain abscess in a neonate. To the best of our knowledge, this is the second case, of C. sedlakii causing complicated meningitis in a neonate in the world.